2022
DOI: 10.1007/s00464-022-09615-x
|View full text |Cite
|
Sign up to set email alerts
|

Suspected common bile duct stones: reduction of unnecessary ERCP by pre-procedural imaging and timing of ERCP

Abstract: Background Endoscopic retrograde cholangiopancreatography (ERCP) is the procedure of choice to remove sludge/stones from the common bile duct (CBD). In a small but clinically important proportion of patients with suspected choledocholithiasis ERCP is negative. This is undesirable because of ERCP associated morbidity. We aimed to map the diagnostic pathway leading up to ERCP and evaluate ERCP outcome. Methods We established a prospective multicenter cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The variation in the MRCP results of diagnosing the CBD stones compared to the ERCP can be attributed to the variation in the MRCP protocol itself. One more explanation was mentioned by Christina et al, 2023 (15) who stated that when additional pre-ERCP imaging was performed (EUS/MRCP), the chance of CBD sludge or stones during ERCP increased. Timing is of importance, and it was revealed that a delay of more than two days between diagnostic imaging (EUS/ MRCP) and ERCP reduces the chance of a positive ERCP.…”
Section: Our Findings Keep With What Was Mentioned Bymentioning
confidence: 99%
“…The variation in the MRCP results of diagnosing the CBD stones compared to the ERCP can be attributed to the variation in the MRCP protocol itself. One more explanation was mentioned by Christina et al, 2023 (15) who stated that when additional pre-ERCP imaging was performed (EUS/MRCP), the chance of CBD sludge or stones during ERCP increased. Timing is of importance, and it was revealed that a delay of more than two days between diagnostic imaging (EUS/ MRCP) and ERCP reduces the chance of a positive ERCP.…”
Section: Our Findings Keep With What Was Mentioned Bymentioning
confidence: 99%
“…However, recent work has shown that when performing ERCP in patients fulfilling these criteria, you may perform ERCP in a significant proportion of patients without bile duct stones. In some, because stones passed spontaneously, in some because there was an alternative diagnosis ( 15 ). As always, a hurdle to optimal patient care is the sensitivity and specificity of our current diagnostic criteria, as stated by the guideline authors in their introduction.…”
Section: Choledocholithiasis In One Stepmentioning
confidence: 99%
“…Se calcula que la sensibilidad de la ESBP es del 97% (IC 95%: 91-99) mientras que su especificidad es del 90% (IC 95%: 83-94), comparado con la CRM con una sensibilidad del 87% (IC 95%: 80-93) y especificidad del 92% (IC 95%: 87-96) (6) con respecto al diagnóstico de coledocolitiasis. De igual manera, el uso de la ESBP sirve como herramienta para disminuir el número de CPRE innecesarias gracias a su alto valor predictivo negativo (VPN) considerando las complicaciones asociadas a esta (7)(8)(9)(10)(11) . En el estudio publicado por Patel et al, la ESBP como primera aproximación diagnóstica evitó la realización de CPRE en un 57,7% de los pacientes (12) .…”
Section: Introductionunclassified